FriDatE: Pengembangan Potensi Kemampuan Debate Mahasiswa Tingkat Karesidenan Madiun - Nimasari, Elok Putri; Gestanti, Rohfin Andria (Aksiologiya: Jurnal Pengabdian Kepada Masyarakat, 2018)
Debate is a competence that must be owned by students because in addition to including a prestigious event, debate as a place for students to think critically (critical thinking) and convey the thought well and systematically. The willingness and ability of good students in debating should be a good quality asset of the young generation. However, their great motivation is hampered if there is no container that they can make a place to develop the skills they already have. FriDatE's community service activities, "Friendly Debate Match and Seminars of Amongst All Varsity Debates of Madiun District" were conducted to introduce students to the debating community at Muhammadiyah University of Ponorogo and the establishment of a university student debate community for the residency of Madiun. In addition, the program also brings in debates experts who can be used as a guide and guide in the debate. The existence of tutors is very helpful for students to evaluate and provide new knowledge about English debate in the next regular meetings.